The Physics of Banjos A Conversation with David Politzer. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and David Politzer, 2004 Nobel Laureate and the Richard Chace Tolman Professor of Theoretical Physics at Caltech. This wide-ranging conversation examines many of the intriguing aspects associated with the physics of banjos, including the ocarina effect, string-stretching, the subtleties of how we hear pitch, transient growth, and the mysterious ringing sound of banjos; while also touching on contemporary issues in black holes and particle physics.This carefully-edited book includes an introduction, Dancing To His Own T.